Auditing and GRC Automation in SAP - Chuprunov, Maxim; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Over the last few years, financial statement scandals, cases of fraud and corruption, data protection violations, and other legal violations have led to numerous liability cases, damages claims, and losses of reputation. As a reaction to these developments, several regulations have been issued: Corporate Governance, the Sarbanes-Oxley Act, IFRS, Basel II and III, Solvency II and BilMoG, to name just a few. In this book, compliance is understood as the process, mapped not only in an internal control system, that is intended to guarantee conformity with legal requirements but also with internal policies and enterprise objectives (in particular, efficiency and profitability). The current literature primarily confines itself to mapping controls in SAP ERP and auditing SAP systems. Maxim Chuprunov not only addresses this subject but extends the aim of internal controls from legal compliance to include efficiency and profitability and then well beyond, because a basic understanding of the processes involved in IT-supported compliance management processes are not delivered along with the software. Starting with the requirements for compliance (Part I), he not only answers compliance-relevant questions in the form of an audit guide for an SAP ERP system and in the form of risks and control descriptions (Part II), but also shows how to automate the compliance management process based on SAP GRC (Part III). He thus addresses the current need for solutions for implementing an integrated GRC system in an organization, especially focusing on the continuous control monitoring topics. Maxim Chuprunov mainly targets compliance experts, auditors, SAP project managers and consultants responsible for GRC products as readers for his book. They will find indispensable information for their daily work from the first to the last page. In addition, MBA, management information system students as well as senior managers like CIOs and CFOs will find a wealth of valuable information on compliance in the SAP ERP environment, on GRC in general and its implementation in particular.
PART I — From Legislation to Concept: ICS and Compliance in the ERP Environment -- Legal Requirements in ICS Compliance -- The Auditor Is Coming: When, Why, and How to Cope -- ICS Requirements and ERP Systems: Basic Principles, Frameworks, Structure -- How Does SAP Deal with Risk- and Compliance-Related Topics? -- PART II — From Concept to Content: Audit Guide for SAP ERP -- Audit-Relevant SAP Basics -- IT General Controls in SAP ERP -- General Application Controls in SAP ERP -- Controls in Financial Accounting -- Control Mechanisms in the SAP ERP-Supported Procure to Pay Process -- Control Mechanisms in the SAP ERP-Supported Order to Cash Process -- Data Protection Compliance in SAP ERP Human Capital Management -- Fraud in an SAP System -- Excursion: FDA Compliance and Controls in SAP -- Examples of Efficiency-Oriented and Profitability-Oriented Analysis Scenarios in SAP ERP -- PART III — From Concept and Content to Implementation: Automation of an Internal Control System -- ICS Automation: How to Set the COSO Cube in Motion -- ICS Automation Using SAP Process Control -- Implementation of Automated Test and Monitoring Scenarios in the SAP ERP Environment -- Experiences from Practice and Projects.
Keywords: Application software; Accounting; Bookkeeping .; Computers; Law and legislation; Management information systems; Computer science; Computer Appl. in Administrative Data Processing; Accounting/Auditing.; Legal Aspects of Computing; Management of Computing and Information Systems; Business IT Infrastructure; Business Information Systems